Perancangan Aplikasi Watermaking dalam Penyembunyian Label Hak Cipta dengan Metode RSPPMC - Manurung, Herman; Gunawan, Indra; Jalaludin, Jalaludin; Sumarno, Sumarno; Nasution, Zulaini Masruro (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This watermaking is a form of steganography that is used to store a digital data into another digital host. One is used to preserve the originality or creativity of the creation of his work. While the method used in designing watermaking on digital imagery is very much, one of them is the method randomly sequenced pulseposition modulated (RSPPMC). The use of this method is done by dividing the principle image of spread spectrum and RSPPMC so that it contains 1 bit of information from the label to match the embed bits of the label. This designed software using Visual Basic programming language 6.0 has been able to do the insertion and reading of copyright labels in digital image images. The most commonly inserted character length is 250 characters, if more of the copyright labels are not perfectly stored.